2008
DOI: 10.1037/0022-006x.76.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Parent-child interactions, peripheral serotonin, and self-inflicted injury in adolescents.

Abstract: Self-inflicted injury in adolescence indicates significant emotional and psychological suffering. Although data on the etiology of self-injury are limited, current theories suggest that the emotional lability observed among self-injuring adolescents results from complex interactions between individual biological vulnerabilities and environmental risk. For example, deficiencies in serotonergic functioning, in conjunction with certain family interaction patterns, may contribute to the development of emotional la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 36 publications
7
112
1
2
Order By: Relevance
“…Researchers in Western countries and China have also reported that self-injurious behaviors among adolescents are strongly associated with their negative moods, psychological traits, and interpersonal interactions (Crowell et al, 2008;Ross & Heath, 2003;Suyemoto & MacDonald, 1995;S. J. Wang, 2010).…”
Section: Research-article2015mentioning
confidence: 99%
“…Researchers in Western countries and China have also reported that self-injurious behaviors among adolescents are strongly associated with their negative moods, psychological traits, and interpersonal interactions (Crowell et al, 2008;Ross & Heath, 2003;Suyemoto & MacDonald, 1995;S. J. Wang, 2010).…”
Section: Research-article2015mentioning
confidence: 99%
“…Indeed, poor family relations have been linked to a number of adolescent psychosocial issues including anxiety disorders (Keeley & Storch, 2009), depression and suicide (Allen, Porter, McFarland, McElhancey, & Marsh, 200;Steinberg & Davila, 2008;Taliaferro, Rienzo, Miller, Pigg, & Dodd, 2008), bipolar disorder (Miklowitz & Chang, 2008), conduct disorder (Chen & Simons-Morton, 2009;Coll et al, 2008;Colman et al, 2009;Jensen, 2008;Laible et al, 2000;Zegers et al, 2008), self injurious behavior (Crowell et al, 2008;Herr, Hammen, & Brennan, 2008), and substance use disorders (Chassin & Handley, 2006;Coll, Thobro, & Haas, 2004;Fromme, 2006;Tucker, Ellickson, & Klein, 2008;Schindler et al, 2005; van der Vorst, Engels, Meeus, Dekovic, & Vermulst, 2006). …”
Section: Cohesion Vs Conflictmentioning
confidence: 99%
“…emotional responses (Crowell et al, 2008;Linehan, 1993). There is a clear lack of studies that simultaneously analyze multiple components to create full accounts of emotion dysregulation in BPD and account for possible theoretical and statistical overlap in a manner similar to the formulation of Linehan's theoretical framework (Carpenter & Trull, 2013;Sadikaj, Russell, Moskowitz, & Paris, 2010).…”
Section: Criteria For a Framework For The Investigation Of Affective mentioning
confidence: 99%